Surface properties and thermal behavior of Malaysian coir fiber - Ahmad, Zuraida (Universiti Sains Malaysia, 2012)
Growing awareness of environmental concerns has encouraged the uses of natural fiber in a product. Natural fibers are extensively used in composite structure replacing synthetic fibers because they are abundantly available, low density, non-toxic and harmlessness, biodegradable, reliable in processing and low cost. Among the various natural fibers, coir fibre has shown a great potential for use in composite structures. Thus, present works study the properties of lignocellulosic fiber (coir fiber) as such attempts to use them as reinforcement in composite components. Considering all above, the chemical composition, morphology and thermal behavior of coir fiber were investigated. Peaks belong to hemicellulose, cellulose and lignin of fiber was identified from the FTIR spectra. The morphology properties of coconut fibers were determined using SEM. The thermal stability of the fibers was measured by means of TG. TG curves revealed degradation of different constituent of the coir fiber.